2016
DOI: 10.1007/s00415-015-8002-2
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal autoantibodies in epilepsy patients with peri-ictal autonomic findings

Abstract: Autonomic dysfunction has frequently been reported in autoimmune encephalitis associated with seizures and there is growing evidence that epilepsy patients may display neuronal autoantibodies (NAAb). The aim of this study was to investigate the frequency of NAAb in epilepsy patients with peri-ictal autonomic findings. Fifty-eight patients (37 women/21 men; average age of 34.2 ± 9.9 years and epilepsy duration of 19.1 ± 9.6 years) who had at least one video-EEG recorded focal or secondary generalized seizure wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 45 publications
2
42
0
Order By: Relevance
“…Patients 1, 2, 3, 4, 13 and 21 were previously reported by Ekizoglu et al 1; patients 6, 7, 12, 16 and 17 were previously reported by Baysal-Kirac et al 24 in this table 1.…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…Patients 1, 2, 3, 4, 13 and 21 were previously reported by Ekizoglu et al 1; patients 6, 7, 12, 16 and 17 were previously reported by Baysal-Kirac et al 24 in this table 1.…”
Section: Resultssupporting
confidence: 64%
“…Patients 1, 2, 3, 4, 13 and 21 were previously reported by Ekizoglu et al 1; patients 6, 7, 12, 16 and 17 were previously reported by Baysal-Kirac et al 24 in this table 1.*Numbers indicate the antibody binding intensity scored visually on a range from 0 (negative) to 4 (very strong).†Indicates patients with a benign course and unexplained remission. ‡Seizure free after operation for 3 years one F- BCS during AED tapering, afterwards seizure-free again since 2007.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…FBDS seems to be related with LGI1 antibodies, since no FBDS was reported in 5 Korean patients with CASPR2 antibodies [Sunwoo et al, 2015]. Even though ictal and peri-ictal dysautonomic features such as tachychardia, blood pressure abnormalities, or hypersalivation are primarily observed in anti-NMDAR encephalitis (see above, Part 1) or Caspr2 encephalitis [Baysal-Kirac et al, 2016], pilomotor seizures [Rocamora et al, 2014] and bradycardia [Naasan et al, 2014] were respectively described in 3/5 and in 3/14 patients in association with LGI1 antibodies.…”
Section: Limbic Encephalitis Associated With Anti-mentioning
confidence: 99%
“…In a thoroughly detailed position statement, Graus et.al lay out the clinical scenarios that should raise suspicion for autoimmune encephalitis/epilepsy, thereby identifying patients with the highest expected yield for antibody testing, but more importantly, those with a clinical picture that would justify treatment for autoimmune encephalitis even while waiting to receive the results of antibody testing. Such efforts to define autoimmune epilepsy on clinical grounds are even more critical as we recognize that patients may be "seronegative" but still have autoimmune epilepsy, given the lag of our knowledge as we are only starting to scratch the surface of this entity and still have many more pathogenic antibodies to discover [2][3][4]8 .…”
mentioning
confidence: 99%